Self-Service Technology Research: A bibliometric co-citation visualization analysis. (July 2019) - Shin, Hakseung; Perdue, Richard R.
Highlights: Bibliometric Article Co-Citation Analysis of self-service technology research. Foundational SST research focused on customers' attitude toward and adoption of the technologies. Turning points focused on understanding customer experiences, service failure and recovery. Research categories: customer SST adoption process, customer value co-creation, and customer SST experiences. Key topics for future hospitality SST research are provided. Abstract: As a value co-creation tool, there is growing adoption of self-service technology (SST) in hospitality. However, SST has received limited hospitality research attention. As a guide for future research, the purpose of this study was to conduct a bibliometric analysis focusing, first, on the hospitality and tourism SST literature, but then expanding to include the broader business SST literatures. The goals of this research were to examine the evolution and current trends in SST research; to identify the studies which have made key contributions to the intellectual foundation, development, and turning points; and to identify key SST research topics, trends, and questions. The analysis covers 199 journal articles published in HTM (n = 23) and the broader business management literature (n = 176) between 2000 and 2017. The results identify foundational articles, turning point articles, and article clusters. The study closes with recommendations for future hospitality SST research as well as theoretical implications.